Enhancing clinical and immunological effects of anti-PD-1 with belapectin, a galectin-3 inhibitor. Issue 4 (9th April 2021) - Curti, Brendan D; Koguchi, Yoshinobu; Leidner, Rom S; Rolig, Annah S; Sturgill, Elizabeth R; Sun, Zhaoyu; Wu, Yaping; Rajamanickam, Venkatesh; Bernard, Brady; Hilgart-Martiszus, Ian; Fountain, Christopher B; Morris, George; et al.
Abstract : Background: PD-1/PD-L1 engagement and overexpression of galectin-3 (Gal-3) are critical mechanisms of tumor-induced immune suppression that contribute to immunotherapy resistance. We hypothesized that Gal-3 blockade with belapectin (GR-MD-02) plus anti-PD-1 (pembrolizumab) would enhance tumor response in patients with metastatic melanoma (MM) and head and neck squamous cell carcinoma (HNSCC). Methods: We performed a phase I dose escalation study of belapectin+pembrolizumab in patients with advanced MM or HNSCC (NCT02575404 ). Belapectin was administered at 2, 4, or 8 mg/kg IV 60 min before pembrolizumab (200 mg IV every 3 weeks for five cycles). Responding patients continued pembrolizumab monotherapy for up to 17 cycles. Main eligibility requirements were a functional Eastern Cooperative Oncology Group status of 0–2, measurable or assessable disease, and no active autoimmune disease. Prior T-cell checkpoint antibody therapy was permitted. Results: Objective response was observed in 50% of MM (7/14) and and 33% of HNSCC (2/6) patients. Belapectin+pembrolizumab was associated with fewer immune-mediated adverse events than anticipated with pembrolizumab monotherapy. There were no dose-limiting toxicities for belapectin within the dose range investigated. Significantly increased effector memory T-cell activation and reduced monocytic myeloid-derived suppressor cells (M-MDSCs) were observed in responders compared with non-responders. Increased baseline expression of Gal-3+ tumor cells and PD-1+CD8+ T cells in the periphery correlated with response as did higher serum trough levels of pembrolizumab. Conclusions: Belapectin+pembrolizumab therapy has activity in MM and HNSCC. Increased Gal-3 expression, expansion of effector memory T cells, and decreased M-MDSCs correlated with clinical response. Further investigation is planned.